Tackling inequalities in health: An agenda for action - Benzeval, Michaela; Judge, Ken; Whitehead, Margaret (Revista Cubana de Higiene y Epidemiología, 1999)
Prólogo realizado por Sir Donald Acheson. Publicado por Kings Fund Publisching, Londres, 1996.